Green Practice in the Supply Chain: The Case of Malaysian Aero Composite Manufacturing Industry - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba (2011)
Green supply chain management is a concept that gaining popularity in the most region in the world. For many organizations, it is a way to demonstrate their sincere commitment to sustainability. In addition, many realize that customers and other stakeholders do not always distinguish between a company and its suppliers. This paper is then, to investigate green supply chain practices in Malaysian aero composite manufacturing companies, as an initiative for environmental enhancement of green management programme in Malaysia which has the potential to offer greater economic value especially in manufacture of composites material components and sub-assemblies for aircraft application. The study indentified that industry are currently do not have enough efforts toward green supply chain and it shows that there is lack of initiative on greening suppliers. However, the industry is struggling to enhance the green activities through continuous improvement programme such as lean manufacturing, as per requested from the customers, stakeholders and ISO practices.